2018
DOI: 10.1002/app.47073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geometry and PVP addition on mechanical behavior of PEI membranes for use in wastewater treatment

Abstract: This study focuses on the mechanical behavior and design of membrane filters that are used in water and wastewater treatment. The aim of this study is, after characterizing the mechanical behavior of the membrane materials, to find a better shape in terms of mechanical parameters. As the first step, uniaxial tensile testing is applied to the produced polymeric membranes with certain contents of poly(ether imide), poly(vinylpyrrolidone), and N-methyl-2-pyrrolidone to get an understanding of the mechanical behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…Adding PVP to PAN increases porosity as well as the surface roughness (RMS, consequently as explained earlier), PWF, viscosity and water content, but decreases the stiffness, strength and contact angle. Similar results with different polymeric material are to be found in the literature [69].…”
Section: Materials Characterisationsupporting
confidence: 91%
See 1 more Smart Citation
“…Adding PVP to PAN increases porosity as well as the surface roughness (RMS, consequently as explained earlier), PWF, viscosity and water content, but decreases the stiffness, strength and contact angle. Similar results with different polymeric material are to be found in the literature [69].…”
Section: Materials Characterisationsupporting
confidence: 91%
“…As mentioned earlier, a significant portion of the research in the literature only prepares and characterises the membranes. Whereas too few of those studies include modelling works with the results they obtain from the characterisation process [69]. These membranes are designed to treat fruit juice wastewater in the "Submerged Membrane Bioreactor" (MBR) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SEM analysis also supports these results by showing the internal structure of PAN 1 membranes with lower porosity. The internal structure of PAN 1 leads to stiffer behaviour, with higher yield and tensile strength compared to PAN 2 [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, this study deals with the numerical modelling of the mechanical behaviour of porous polymeric membranes relying on the data acquired from the experiments that are conducted on the manufactured membranes. As mentioned earlier, a significant portion of the research in the literature only prepares and characterises the membranes, whereas too few of these studies include modelling works with the results they obtain from the characterisation process [ 69 ]. These membranes are designed to treat fruit juice wastewater in a “Submerged Membrane Bioreactor” (MBR) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of PVP is also considered as it affects the membrane characteristics [47]. Tufekci et al have investigated the mechanical behaviour of PVP-added polyetherimide (PEI) membranes under uniform pressure using the finite element method, and they reported that the most mechanically favourable membrane is elliptical [48]. In their next study, Tufekci et al found that the von Mises stress decreased and the mechanical performance increased with the increase in the aspect ratio of the PVP-doped PAN elliptical membranes in the elastic zone under uniform pressure [49].…”
Section: Introductionmentioning
confidence: 99%